Study on the flow field and structural stress field of the primary retarder considering the throttling characteristics of the valve - Huanhui Zhou; Zilin Ran; Hu Dai; Weida Yang; Xianwei Chen (Advances in Mechanical Engineering)
The valve plays an important role in the control of the filling rate ( q fill ) and braking characteristics of the hydrodynamic retarder (HR). However, the dynamic throttling characteristics of the valve were rarely considered in previous studies. Therefore, this paper considers the influence of the external valve system (retarder valve) of HR on its flow field, structural field and braking characteristics. Firstly, numerical calculation and experimental verification are carried out on the flow passage model without inlet and outlet (Plan A), with inlet and outlet (Plan B) and with retarder valve (Plan C). After considering the throttling characteristics of the retarder valve, the maximum errors of the impeller rotational speed ( n ), q fill and braking torque ( T ) characteristic curves are 2.678% and 3.517%, respectively, and the average errors are 4.526% and 5.012%, respectively. Compared with the other two schemes, the average error and maximum error of HR have been greatly reduced. Then, this paper compares the differences between the three schemes from the perspective of flow field and structural field, and expounds the influence of retarder valve on the numerical calculation results of retarder from the internal mechanism. Finally, this paper discusses the influence of n, q fill and retarder valve opening on the calculation results of Scheme C. The results show that the opening of the valve port will seriously affect the flow rate at the inlet of HR, and the flow rate in the retarder valve will have a hysteresis effect on the circulation flow in the mainstream region of HR. The research method of this paper can provide reference for the numerical study of turbomachinery.